2022
DOI: 10.1111/jdv.18570
|View full text |Cite
|
Sign up to set email alerts
|

Changing spectrum of hair and scalp disorders over the last decade in a tertiary medical centre

Abstract: Background: Hair-and scalp-related disorders (HSRDs) encompass a wide range of conditions that affect people of all ages.Objective: To evaluate the workload and trends in HSRDs at an outpatient dermatological clinic in a tertiary medical centre over a 10-year period.Methods: Medical records for HSRD visits to the outpatient dermatology clinic at the Sheba Medical Center, an Israeli tertiary care center, were reviewed between 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…An Israeli skin clinic reported that hair loss-related visits increased from 1.24% in 2010 to 9.44% in 2020. Furthermore, the highest increase was noted in the prevalence of androgenetic alopecia (AGA), from 17% in 2010 to 32% in 2020 35 . Safavi et al 36 indicated that the estimated incidence of AA was 20.2 per 100,000 person-years from 1975 to 1989.…”
Section: Current Hair Loss Situationmentioning
confidence: 99%
“…An Israeli skin clinic reported that hair loss-related visits increased from 1.24% in 2010 to 9.44% in 2020. Furthermore, the highest increase was noted in the prevalence of androgenetic alopecia (AGA), from 17% in 2010 to 32% in 2020 35 . Safavi et al 36 indicated that the estimated incidence of AA was 20.2 per 100,000 person-years from 1975 to 1989.…”
Section: Current Hair Loss Situationmentioning
confidence: 99%
“…A study of Korean men documented that the average age of men who developed AGA in the years from 2006 to 2010 decreased from 34.1 to 31.6 years [92]. A study of a population in Israel over the course of a decade (2010-2020) measured an increased rate of AGA from 17% to 32% [93] in the general population.…”
Section: Perspectives On the Culture Of Hair Care In Africamentioning
confidence: 99%
“…The highest disease prevalence (10–50%) is reported in children, in particular those with a positive family history of AA [ 6 ]. An increasing number of patients visit tertiary dermatology centers due to AA, the second most common form of non-cicatricial alopecia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%